Biodegradable polymeric implants as drug delivery systems for brain cancer therapy - Norased Nasongkla (2018)
Brain cancer therapy has been a challenging task due to its fatal outcome and limited accessibility. Recent advance in DDS leads to the utilization of polymers for the local delivery of anticancer agents directly to brain tumors. Polymer has received a growing attention as a material for drug delivery systems (DDS), especially brain cancer because of its biodegradable and biocompatible properties. Ease of polymer synthesis makes it possible to tune polymer properties to provide different drug release profiles and degradation mechanisms. This review aims to provide the information concerning biodegradable polymeric implants. The main focus is on systems that currently reach the in vivo study or are using in clinic. © 2009 Springer-Verlag.